Advances in Antibiotic-Loaded Nanofibers for the Treatment of Bone Infections: A Review - Imanto, Teguh; Nonni Soraya Sambudi; Khadijah Zai; Teuku Nanda Saifullah Sulaiman (Universitas Muhammadiyah Surakarta, 2024)
Antibiotic-loaded nanofiber-based drug delivery systems represent a novel approach to treating complex bone infections, particularly osteomyelitis caused by antibiotic-resistant bacteria such as Methicillin-resistant Staphylococcus aureus (MRSA). These systems offer localized, sustained drug release, significantly reducing systemic side effects and mitigating the development of antibiotic resistance. This review evaluates advancements in electrospun nanofibers with biodegradable polymers like Poly(lactic-co-glycolic acid) (PLGA) and Polycaprolactone (PCL), which ensure controlled drug release while supporting bone regeneration. A systematic search using PRISMA guidelines across ScienceDirect and ACS Publication databases (2020-2024) identified 42 relevant studies. The inclusion of bioactive agents such as hydroxyapatite in nanofibers was found to enhance antibacterial properties and accelerate tissue regeneration. The review demonstrates that antibiotic-loaded nanofibers offer a promising, targeted therapeutic alternative to conventional treatments, particularly for osteomyelitis and similar challenging bone infections. Future research directions will focus on optimizing nanofiber compositions and functionalities to better meet clinical needs, ensuring more efficient and personalized management of severe bone infections.